A Critical Assessment of Israel-Hamas War in the Israel-Palestine Conflict - Oluwashakin, Ajinde; Aboyade, Ariyo S. (Journal of Contemporary International Relations and Diplomacy, 2024)
At dawn on Saturday, October 7, 2023, the Hamas militant Palestinian group, that controlled the Gaza Strip since 2007, launched dastardly surprise attacks on Israel. It was the deadliest attack on the State of Israel since its War of Independence in 1948 and the Yom Kippur War in 1973. This paper critically examined the Hamas phenomenon in the war and the possibility of achieving a Palestinian State, not by war but by diplomatic engagement of all stakeholders. The theory of Fourth Generation Warfare is adopted to understand the situation better in the Israel-Palestine conflict, and particularly the Hamas war strategy. The study adopted a qualitative research approach for an in-depth exploration of perspectives, experiences, and narratives related to the conflict. It gathered data from documentaries, articles from learned journals, the mediascape, government official statements and websites, to capture the diverse viewpoints and narratives surrounding the conflict and war. The international media watch has tracked the battlefield exchanges (reports) and diplomatic shuttles between major stakeholders’ capitals. The Gaza Strip enclave has suffered monumental destruction and a horrific humanitarian catastrophe. Ceasefire had met with stiff opposition from the combatants. The conclusion is that Palestinian struggles for statehood since 1948 had hardly led them to achieve their goal. Given the generational historicity of the conflict, it is hard to decipher whether war or diplomacy would eventually bring about peace. But efforts must be continued on the diplomatic channels to manage the conflict.